Avaliação da estrutura de um fragmento florestal no município de Catende, PE - GUIMARÃES, Francisco José Pimentel (2005)
The main goal of this study was to evaluate the structure of a forest fragment in the municipal district of Catende/PE, seeking to subsidize future actions that can conserve and/or recover the forest fragment of Usina Catende. The study was accomplished in the fragment denominated “Forest of the Chinkens”, located in the Engenho Huimatá. The phytosociologic structure was determined with use of 14 plots of 10x25m (250m2), distributed in parallel lines with 50 meters among lines and plots. It was measured all the sampled trees with circumferences at the breast height (CBH) equal or superior to 10 cm. In the trees with bifurcation all the trunks were measured. The following phytosociologic variables were measured: density, frequency, dominance, importance value (IV) and sociological position. The estimate of the phytosociologic parameters were obtained with the use of the software “Native Forest”. The analysis of sampling sufficiency of the floristic composition was accomplished through the methodology of the specie distribution curves by area. For the diameters and height distribution it was considered class of 5 cm and 2 m, respectively. With the sample sufficiency accomplished it was observed 438 tres/3.500m2 with 63 species distributed in 29 families which 46 were identified at the species level, 11 at gender level, 2 at the family level e 4 were not identified. The families that presented larger frequency were Moraceae, Lecythidaceae,Mimosaceae and Anacardiaceae. The fragment presented index of diversity of Shannon-Weaver of 3,43 nats./ind. being compatible with other studies in Pernambuco. The ten species with larger values of IV were Brosimum discolor, Parkia pendula, Eschweilera ovata, Thyrsodium spruceanum, Tapirira guianensis, Protium heptaphyllum, Casearia arborea, Helicostylis tomentosa, Dialium guianense and Schefflera morototoni, tha represented 57,99; 41,74; 64,60 and 54,78%, of density, frequency, dominancy and importance value of the total sampled species. In the evaluation of the height it was observed a minimum height of 3,6 m and maximum of 22,00 m, with average of 8,67 m and standard deviation of 4,04 m. it was verified that 10 species were in three strata: Brosimum discolor, Brosimum sp.,Casearia arborea, Cecropia palmata, Dialium guianense, Escweilera ovata, Himatanthus phagedaenicus, inga fagifolia, Protium heptaphyllum and Thyrsodium spruceanum. The studied fragment presents low floristic diversity although it presents compatible diversity with other studies accomplished in Atlantic Forest. The families of larger importance in the study were Moraceae, Anacardiaceae and Lecythidadeae. Among the main sampled just the Brosimum discolor, Eschweilera ovata and Thyrsodium spruceanum presented a regular sociological position. The total diameter structure was similar to even aged forests, with the distribution in decreasing geometric form (inverted J). The studied fragment possesses little relevance; however, if considered jointly with other fragments of the area, its diversity is significant, justifying efforts to its conservation and management in landscape scale.